Keputusan Pembelian Produk Air Minum Dalam Kemasan di Wilayah Jakarta Utara - Tatiana, Yana; Andini, Dinda Ayu; Sulistyaningsih, Erny; Setyawati, Aswanti; Affiat, Muhammad Riza (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2024)
Currently, there are many similar bottled drinking water products that have been competing with each other for several years and and become consumers' doubts in choosing several Aqua products and their competitors. There has been increasing competition among several companies, especially bottled drinking water, and companies have to improve product quality and maintain their brand image regarding consumer purchasing decisions. The aim of this research is to analyze how much influence product quality and brand image have on purchasing decisions for bottled drinking water products at PT Tirta Investama with the Aqua brand. This research uses a quantitative approach with multiple linear regression analysis tools. The number of samples in the North Jakarta area with a sample of 399 respondents using a cluster random sampling technique, namely people who consume the Aqua Company's bottled drinking water. From the research results, it was concluded that product quality and brand image each partially have a positive and significant effect on purchasing decisions. Meanwhile, simultaneously product quality and brand image have a positive and significant effect on purchasing decisions